Interior shell patterns among the Spondylid species (Bivalvia: Spondylidae) in Mindanao, Philippines - FABIO JR. C. RUAZA; DONARD C. MATURAN; ERMELYN BUSTILLO (Biodiversitas Journal of Biological Diversity, 2024)
Abstract. Ruaza FJC, Maturan DC, Bustillo E. 2024. Interior shell patterns among the Spondylid species (Bivalvia: Spondylidae) in Mindanao, Philippines. Biodiversitas 25: 2901-2906. The variations among the species of the Spondylus were assessed based on its interior shell pattern using landmark-based geometric morphometry. A total of 200 specimens were subjected to analysis. Samples of the Spondylid species were collected and photographed, and 15 landmarks from internal shell morphology were quantified and analyzed. The landmarks include the umbo, teeth, size of the muscle scar, and the pallial sinus. Multivariate analysis of variance revealed significant differences in internal shell characters among Spondylid species across sampling sites (p<0.05). Canonical Variance Analysis (CVA) effectively differentiated the local Spondylid species into distinct clusters. In addition, the relative warps captured the most significant sources of variation in the morphological characters analyzed, leading to effective differentiation between the groups or populations of the species. The most distinguishing characteristics among the species are the distance of the pallial line to the ventral tip of the adductor muscle scar and the size of the cardinal tooth. The internal shell characters among the Spondylid species exhibit notable disparity despite their great morphological similarity. These shell characters can be used in the identification while conservation efforts are still in the initial stage of development. The presence of notable dissimilarities in the internal shell characteristics among the Spondylid species indicates that even slight deviations can result in noticeable morphological distinctions. This discovery enhances the understanding of the species divergence within this group and underscores the significance of incorporating internal shell characteristics into taxonomic and ecological investigations.